Działania władz terenowych oraz aparatu bezpieczeństwa wobec placówek oświatowo-wychowawczych ss. salezjanek w Łodzi i ich likwidacja - Kolasa, Krzysztof (Pamięć i Sprawiedliwość, 2010)
During People’s Poland (the People’s Republic of Poland) after having dispose of the independent underground and the overt political opposition, Communistic authorities started the fight against the Catholic Church. Its spiritual influence on children and adolescents was being systematically eliminated by reducing religion classes and elimination of the Catholic educational-tutorial institutions. These repercussions were also felt by Catholic convents, especially by the Convent of the Daughters of Mary Help of Christians (The Salesian Sisters), which sisters during the 1930-1939, in the house at 85 Franciszkańska street, in Lodz established and were keeping (running) nursery school, workshops, school, oratory and youth associations. Shortly after World Word II they rearranged and re-brought to the life educational-tutorial institutions which were liquidated during the German occupation. In 1948 “Ochronka Bałucka” (the shelter located in Białuty district in Lodz, where children from the poorest families could gather to play together, learn, pray and hide from harm) was finally liquidated, as well as sodality and oratory – probably in the next year. In 1952 the territory authorities seized the nursery school, while in 1963 the Vocational School of Clothing (Zasadnicza Szkoła Odzieżowa) which was the last Catholic educational institution in Lodz, was eventually closed. Practically from 1948 until 1963, the Salesian Sisters in Lodz were struggling constantly to maintain the operation of their ongoing educational works. The activity of the territory authorities and of the Security Apparatus in Lodz took various forms and methods like: inspections, bans on the recruitment of female students to the 1st class of the primary school, using various types of pressure, which consequently led to the removal or resignation of the work the most resistant teachers (for example sister Maria Lipińska – the headmaster of the school), attempts of creating communistic youth organizations, persuading into organizing chats, wall magazines, rallies, events and celebrations of occasional national holidays, rivalling in work between female school students, calling for nuns for „talks” which took place in the Department for Religious Affairs (Wydział ds. Wyznań) and in the office of the security service and also attempts of recruitment new members into the net of secret service agents as well as taking control over the most indomitable Salesian Sisters.